About Uzbek Folk Tales and Their Educational Importance - Anvar Allambergenov (International Journal Of Literature And Languages, 2025)
This article discusses one of the genres of Uzbek oral folk art — the fairy tale. It analyzes the process of creation and narration of fairy tales, the diversity of their themes, as well as their educational and spiritual significance. The article highlights the impact of fairy tales on the psyche, their interpretation, and their role in Uzbek culture. This article provides an in-depth analysis of Uzbek folk tales, one of the most important and ancient genres of oral folk literature. Folk tales are regarded as a vivid reflection of the people’s worldview, dreams, and aspirations. They portray high human values such as kindness, justice, courage, friendship, loyalty, diligence, experience, and wisdom through artistic imagery. The article examines the process of the creation and oral transmission of tales across generations, the style of storytelling, the emotional and artistic connection between the narrator and the audience, and the classification of tales into different thematic types – such as magical-fantastic tales, animal tales, and everyday tales.